On Fixed Point Results in Controlled Metric Spaces - Jamshaid Ahmad; Abdullah Eqal Al-Mazrooei; Hassen Aydi; Manuel De la Sen (Journal of Function Spaces)
In this article, we introduce Reich type contractions and (α,F)-contractions in the class of controlled metric spaces and establish some new related fixed point theorems. Our results are generalizations of some known results of literature. Some examples and certain consequences are given to illustrate significance of presented results.